Middle East and North Africa Economic Monitor, April 2017 : The Economics of Post-Conflict Reconstruction in MENA - Devarajan, Shantayanan; Mottaghi, Lili (Washington, DC: World Bank, 2017)
Plagued by war, violence and low oil prices, economic activity in the Middle East and North Africa (MENA) region remained subdued between 2013 and 2015, but the situation is expected to improve and growth to surge above 3 percent over the forecast period. Though still below potential, the improvement in growth offers hope. We see signs of "green shoots" in some countries in the region, therefore we have upgraded our short-term prospects for MENA from "cautiously pessimistic" to "cautiously optimistic" over the forecast period. The prospects of peace in Syria, Yemen and Libya are one of the keys to resuming growth over the next decade. But realizing that potential depends crucially on how the post-conflict reconstruction is conducted. On the one hand, a well-managed process could help these war-tom countries rebuild their shattered economies and re-integrate their people so that the region as a whole, and possibly the rest of the world, benefits. On the other hand, a badly managed process can risk a recurrence of conflict, continued stagnation and suffering, and perpetual fragility. The economics of postconflict reconstruction, therefore, is critical to the future of MENA's economies.